DIE SPRACHE UND DAS PHÄNOMEN HÖFLICHKEIT AM BEISPIEL EINES YOUTUBE-INTERVIEWS English Title: THE LANGUAGE AND THE PHENOMENON OF POLITENESS IN THE CONTEXT OF A YOUTUBE INTERVIEW - Gëzim Xhaferri; Biljana Ivanovska (Journal of Languages for Specific Purposes, 2024)
The aim of this paper is the language analysis of an online-YouTube-interview, where the politeness is defined as a sociocultural entity. In this paper, the most influential theories of politeness are presented and the concept of face is explained. In addition to this, it presents in detail the difference between the positive and negative politeness. The data shows that politeness influences the choice of language means and how the language means can change the communicative situation where the functions of language means in adapting language are illustrated and shown.The results are based on an online-YouTube-interview which is analyzed linguistically by defining and showing the relationship between the participants in the given communication. It also shows how the speakers adapt the politeness forms in relation to the conversation partner. The analysis of the language of the moderator and the guest confirms the assumption that the language is related to the situational context and that the speakers adapt their language depending on the communicative situation, which has been shown by the tendency of the moderator and the interviewed guest to reduce distance, through the use of interpersonal discourse markers as well as other language means.